Late preterm antenatal corticosteroids in singleton and twin gestations: a retrospective cohort study - Luciana A. Vieira; Yu-Han Kao; Despina S. Tsevdos; Yan Kwan Lau; Zichen Wang; Shilong Li; Amanda B. Zheutlin; Susan J. Gross; Joanne L. Stone; Siobhan M. Dolan; Eric E. Schadt; Li Li (BMC, 2022)
Abstract Background In 2016, the American College of Obstetricians and Gynecologists recommended antenatal corticosteroids in the late preterm period for women at risk for preterm delivery. Limited real-world evidence exists on neonatal outcomes, particularly for twin gestations, following the guideline change. The study objective is to determine the association of antenatal corticosteroids in late preterm singleton and twin pregnancies with respiratory complications and hypoglycemia in a real-world clinical setting. Methods This is a retrospective cohort study comprising late preterm deliveries (4,341 mother-child pairs) within the Mount Sinai Health System, 2012-2018. The exposure of interest is antenatal corticosteroid administration of betamethasone during pregnancy between 34 0/7 and 36 6/7 weeks. Our primary outcomes are neonatal respiratory complications and hypoglycemia. Multivariable logistic regression was used to estimate the association between antenatal corticosteroid exposure and these two outcomes. We stratified the study population by singleton gestations and twins to minimize the potential confounding from different obstetric management between the two groups. Results Among a total of 4,341 mother-child pairs (3,309 singleton and 1,032 twin mother-child pairs), 745 mothers received betamethasone, of which 40.94% (305/745) received the full course. Relative to no treatment, a full course of betamethasone was associated with reduced odds of respiratory complications (OR = 0.53, 95% CI:[0.31-0.85], p < 0.01) and increased odds of hypoglycemia (OR = 1.86, 95%CI:[1.34-2.56], p < 0.01) in singletons; however, the association with respiratory complications was not significant in twins (OR = 0.42, 95% CI:[0.11-1.23], p = 0.16), but was associated with increased odds of hypoglycemia (OR = 2.18, 95% CI:[1.12-4.10], p = 0.02). A partial course of betamethasone (relative to no treatment) was not significantly associated with any of the outcomes, other than respiratory complications in twins (OR = 0.34, 95% CI:[0.12-0.82], p = 0.02). Conclusions Exposure to antenatal corticosteroids in singletons and twins is associated with increased odds of hypoglycemia. Among singletons, exposure to the full dosage (i.e. two doses) was associated with decreased odds of respiratory complications but this was only the case for partial dose among twins. Twin gestations were not studied by the Antenatal Late Preterm Steroids trial. Therefore, our study findings will contribute to the paucity of evidence on the benefit of antenatal corticosteroids in this group. Health systems should systematically monitor guideline implementations to improve patient outcomes.